A novel peripheral biomarker for mild cognitive impairment and Alzheimer's disease: Biomarkers (non‐neuroimaging) / novel biomarkers. (7th December 2020) - Parra, Mario A; Schumacher, Marcela; Fernández, Gerardo
Abstract: Background: Recent evidence suggests that oculomotor behaviours linked to cognitive performance can be a biomarker of Alzheimer's disease (AD). Short‐Term Memory Binding (STMB) declines in patients with AD dementia and in those at risk of dementia. STMB relies on brain regions relevant to visual processing which are known to support oculomotor behaviours. A combined analysis of oculomotor responses during STMB can enhance the sensitivity of the assessment of patients with AD or at risk of AD such as those with Mild Cognitive Impairment (MCI). We investigated this hypothesis. Methods: Using eye‐tracking technologies, we measured pupil dilation, fixation, and exploratory eye movement behaviours in patients with AD, MCI and in healthy controls while they performed the STMBT. The STMBT assesses the ability to temporarily hold bicoloured objects whose colours had to be remembered either as individual features (baseline) or integrated within unified representations (binding). Results: Experiment 1 involved 18 healthy older adults and 18 patients with AD dementia. We observed (1) altered pupil dilation linked to poor STMB performance in AD patients. Experiment 2 involved 42 healthy older adults and 63 patients with MCI. Impaired fixation and exploratory eye movement behaviours accompanied poor STMB abilities in MCI patients. Conclusion: Taken together, the results above suggest that eye‐tracking measures combined with cognitive markers for AD (STMBT) can (1) enrich the clinical phenotype of this type of dementia, (2) unveil novel features of AD dementia unknown to date, and (2) provide more sensitive tools which can detect and trace aspects of such phenotype in people at risk, thus helping to ascertain the presence of the prodromal stages of the disease.